ANALISIS YURIDIS PENERBITAN SERTIFIKAT FIDUSIA PADA PERJANJIAN PEMBIAYAAN KENDERAAN BERMOTOR YANG MENGALAMI KEMACETAN PEMBAYARAN (STUDI PADA PERUSAHAAN PEMBIAYAAN DI KOTA MEDAN) - TANJUNG SIMANJUNTAK (PREMISE LAW JURNAL, 2014)
ABSTRACT Law No.42/1999 on Fiduciary Collateral (UUJF) is stipulated to meet legal need and to give legal certainty and legal protection for any stakeholders, particularly for financing companies as creditors and for consumers as debtors. The result of the research showed that financing companies as creditors complied with the regulation stipulated by the government through the Regulation of the Minister of Finance No. 130/PMK.010/2012 on the Registration of Fiduciary Collateral for Financing Companies which Finance Consumers in Buying Motor Vehicles with Fiduciary Collateral as the Mortgage. So far, this case has run smoothly since it is obeyed by financing companies.   It is recommended that the Government socialize the meaning and function of fiduciary registration to financing companies and to all people who use the service of financing companies so that the implementation of law enforcement in UUJF can be done in order that the sense of comfort and fairness can be carried out. Keywords: Fiduciary Registration, Financing Companies